The Seven Steps: Building the DiGA Thesaurus - Serena Autiero; Frederik Elwert; Cristiano Moscatelli; Jessie Pons (Journal of Open Humanities Data, 2023)
This article presents the creation of the ‘Digitization of Gandharan Artefact Thesaurus’, a digital resource for the description of Gandharan art and – more generally – of Buddhist art. It was developed by the project ‘Digitisation of Gandharan Artefacts: A project for the preservation and the study of the Buddhist art of Pakistan’ (DiGA). This work has been realized by walking Seven Steps, a serendipitous coincidence pairing our work to a famous episode in the early life of the Buddha. Our Seven Steps are: • Collection and selection of sources, both digital and printed. • Creation of the core of the Thesaurus by digitizing the Repertorio Iconografico per la schedatura dell’arte gandharica. • Modifying, enriching, and structuring the Repertorio in RDF/SKOS. • Implementation of a hierarchy of concepts for narrative scenes (“narratives”). • Implementation of a hierarchy of concepts for characters (“figures”). • Comparison and reconciliation with other already existing digital thesauri. • Collaboration with other projects and institutions. The DiGA Thesaurus marks an important milestone towards a new vision of Gandharan studies in which the availability of digitized collections will foster new insights and understanding. Already during the creation of the Thesaurus, exciting new perspectives have opened in the field of both Gandharan studies and digital humanities.